Implementasi Sport Education Model terhadap Tingkat Pemahaman Siswa dalam Pembelajaran Permainan Sepak Bola - Baihaki Padika Fajar; Siswanto Siawanto; Akhmad Dimyati (Universitas Hamzanwadi, 2026)
This study was motivated by the gap between students’ procedural mastery of basic soccer techniques and their conceptual understanding of when and why those techniques are applied in actual game situations. The study aimed to examine the effect of implementing the sport education model on students’ level of understanding in soccer instruction at SMAN 1 Telukjambe Barat. The research method employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 27 11th-grade students selected through purposive sampling. The instrument was a 40-item multiple-choice test based on seven revised Bloom’s Taxonomy indicators of understanding. Data were analyzed using the Shapiro-Wilk test, Paired Sample t-test, and N-Gain. The results showed an increase in the average comprehension score from 26.96 to 34.56. The Paired-Sample t-test revealed a significant difference between the pretest and posttest (t = -8.422; df = 26; p = 0.000). An N-Gain value of 0.567 indicates moderate effectiveness. The decrease in standard deviation from 5.13 to 3.11 indicates a more even distribution of understanding among students. All seven indicators of understanding improved, with the “interpreting” indicator showing the greatest improvement. The conclusion of this study is that the implementation of the Sport Education Model has a significant effect on improving students’ level of understanding in soccer instruction.